(3fbW GdYQhSs - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3bGd CHh YHO Gddg GdMejOi , bGd GdEeGe CHh eMeO Ydi Hf CMeO Hf SYjO GdMGaX (B: (3cGf JCdja gPG GdcJGH MOhO GdYTQjf hCQHYeGFg s
(3PcQ ajg CSeGA GdNdaGA ai GdeTQb hGdeZQHs
(3hHChdgG QSGdI ai GdfaS dYdgG dGHf LRe ai (B3 (3hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B170 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs